HUBUNGAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PJOK SISWA KELAS XI MADRASAH ALIYAH NEGERI 2 BATUMANDI KABUPATEN AGAM - Rahmad, Jumadur; Hendri Neldi; Asep Sujana Wahyuri; Abdur Rohim Fadlan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is the suboptimal learning outcomes of Physical Education (PJOK) of class XI students of Madrasah Aliyah Negeri 2 Batumandi, Agam Regency, which is thought to be related to student learning motivation. This study aims to determine the relationship between learning motivation and learning outcomes of PJOK of class XI students of Madrasah Aliyah Negeri 2 Batumandi, Agam Regency. This study uses a correlational method that aims to determine the relationship between the variables studied. The study population was all class XI students of Madrasah Aliyah Negeri 2 Batumandi, Agam Regency. The sample was determined using a simple random sampling technique, resulting in 30 students as research samples. The instruments used were a learning motivation questionnaire and PJOK report card scores. Data were analyzed using the Product Moment correlation technique. The results showed that there was no significant relationship between learning motivation and learning outcomes of PJOK of class XI students of Madrasah Aliyah Negeri 2 Batumandi, Agam Regency. This is evidenced by the correlation coefficient value of r count of 0.165 which is smaller than r table of 0.361 at a significance level of 0.05. Thus, learning motivation did not show a significant relationship with physical education (PJOK) learning outcomes in this study. Based on these findings, the researcher provides suggestions for PJOK teachers to implement more engaging learning and provide more opportunities for practical training.